Induction of Adipogenesis by External Volume Expansion. Issue 1 (January 2016) - Lujan-Hernandez, Jorge; Lancerotto, Luca; Nabzdyk, Christoph; Hassan, Kazi Zayn; Giatsidis, Giorgio; Khouri, Roger K.; Chin, Michael S.; Bassetto, Franco; Lalikos, Janice F.; Orgill, Dennis P.
Abstract : Background: External volume expansion by suction is used to prepare the recipient site for fat grafting by increasing its compliance and vascularity. The authors previously developed a mouse model for external volume expansion and demonstrated its pro-proliferative and angiogenic effects. Increased thickness of the subcutaneous tissue was also observed. This study was thus designed to assess the adipogenic potential of external volume expansion stimulation. Methods: A miniaturized external volume expansion device consisting of a rubber dome connected to a −25 mmHg suction source was applied to the dorsum of mice for a single 2-hour stimulation or for 2 hours daily for 5 days. Tissues were harvested up to 48 hours after the last stimulation and analyzed for edema, inflammation, and adipocyte content by staining for hematoxylin and eosin, CD45, and perilipin-A. Expression of peroxisome proliferator-activated receptor-γ (proadipogenic factor) and preadipocyte factor 1 (preadipocyte marker) was evaluated by Western blot analysis. Results: Both a 2-hour stimulation and cyclical 2-hour stimulation for 5 days induced 1.5- and 1.9-fold increases in the number of adipocytes per millimeter. Edema was present in the immediate poststimulation period, and inflammation was seen 2 days later. Peroxisome proliferator-activated receptor-γ was increased at the end of stimulation. Conclusions: Stretch is known to stimulate proliferation, whereas edema and inflammation are both emerging proadipogenic factors. Their combination in external volume expansion seems to produce proadipogenic effects, seen even after a single 2-hour stimulation. Abstract : Supplemental Digital Content is available in the text.